Marketing research for the tourism, hospitality and events industries - Kolb, Bonita M. (Routledge, 2025)
This user-friendly textbook covers qualitative, quantitative and social media research methods to provide students and course leaders with an accessible guide for learning and teaching marketing research from start to finish.The second edition of this textbook has been updated to include: New content on digital research, social media research methods, emerging technologies such as AI in marketing research, sustainability in tourism, hospitality and events research, thematic analysis, real-time research and researching current visitor trends, experiences, preferences and lifestyles to ensure the destination or event is successful New international short case studies to showcase real-life applications where market research can be used to attract and retain visitors for tourism, hospitality and events This holistic, concise and accessible textbook is essential reading for all students to gain knowledge as to what visitors want from the travel, hospitality and/ or event experience and how to influence a destination's success.